Influence of Geodynamic Processes on Reservoir Properties of Geological Environment (on the Example of the Romashkino Field) - A.A. Dragunov; R.S. Mukhamadiev; S.V. Chernov (Georesursy, 2017)
A significant contribution to the structure of the hydrocarbon deposits can be made by fracturing, which is in the active state under the external stresses relative to the Earth (the lunar-solar gravitational action, the total rotational field of the Earth’s stresses, etc.). On the example of comparing the results of system-geodynamic interpretation with reservoir properties of the Bobrikovian, Timanian and Pashian horizons of the Romashkino field using mathematical-statistical analysis, it has been shown that geodynamic activity significantly affects the reservoir properties. Improvement of reservoir productivity is noted in the areas of mutual overlap of geodynamically active zones of dislocations (DAZD) of various orders and strike, which is recommended to be taken into account both in exploration and development of hydrocarbon fields. Consideration of the geodynamic situation, carried out using the results of system-geodynamic interpretation, will allow the most rational use of various methods of oil extraction at operation sites. The results of system-geodynamic zoning should be used in solving a wide range of oil and gas exploration and operational problems, where the development of fractured zones is important. They can be used both for the search and exploitation of hydrocarbon deposits in conventional carbonate and terrigenous reservoirs, and in non-conventional reservoirs, where the main reservoir properties are determined by fractures.